2019
DOI: 10.4067/s0718-381x2019000100019
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability of Acrylic Resin Teeth After Immersion in Staining Solutions

Abstract: The objective of this study was to evaluate the color alteration of four brands of artificial teeth (Art Plus, Trilux, Bionote and Biolux), after immersion in color solutions of coffee, red wine and urucum. We used 80 artificial teeth, which were standardized with 2 mm thickness. Then, they were subjected to finishing and polishing, and divided into 4 groups (n = 05), which were immersed in one of the 3 types of dye, plus distilled water (control). The samples were immersed daily for 4 hours, then they were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…In the case of Yemeni coffee immersion, the observed mean color change (ΔE) values (yellowish) were between 6.4 and 11.4. This result is in accordance with those of Maranhão et al [ 31 ] and Raja et al [ 17 ]. Coffee contains components called tannins, which are a type of polyphenol that breaks down in the water.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the case of Yemeni coffee immersion, the observed mean color change (ΔE) values (yellowish) were between 6.4 and 11.4. This result is in accordance with those of Maranhão et al [ 31 ] and Raja et al [ 17 ]. Coffee contains components called tannins, which are a type of polyphenol that breaks down in the water.…”
Section: Discussionsupporting
confidence: 94%
“…This result is in agreement with those of Nuaimi and Ragab [ 25 ], Özdaş et al [ 16 ] and Choi et al [ 30 ] on the color stability of composite resin restorative materials, which have suggested that the color stability of these resins is unpredictable over a long period of time and affected by the composite type and storage time, with most of the resins showing unacceptable color changes over time. Maranhão et al [ 31 ] suggested that the composition of the composite restoration, type of pigmenting solution, and immersion time determine the color change.…”
Section: Discussionmentioning
confidence: 99%